PSMA-targeted [(18)F]DCFPyL PET/CT-avid lesions in a patient with prostate cancer: Clinical decision-making informed by the PSMA-RADS interpretive framework - Reyes, Diane K. (Urol Case Rep, 2019)
We present the case of a man with oligometastatic prostate cancer who underwent a PSMA-targeted 18F-DCFPyL PET/CT scan in order to illustrate how the PSMA-RADS grading sytem can be successfully used to support clinical decision-making and treatment planning. Notably, the presented patient was found to have an equivocal bone lesion (PSMA-RADS-3B) which was further worked up with a tumor protocol MRI and found to be definitively benign (PSMA-RADS-1B) and thus removed from the oligometastatic treatment plan. Remaining avid lesions were incorporated into the treatment plan or deferred for later work-up or monitoring, as indicated within the PSMA-RADS framework.